Perkembangan Religiusitas Anak Berkebutuhan Khusus (Tunagrahita) di Sekolah Umum - Amin, Munirul (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2023)
This research was conducted to determine the development of religiosity of children with special needs (ABK), and also to find out what forms of special assistance are appropriate for children with special needs in public elementary schools that have inclusion services. The method used in this research is qualitative with case studies as the approach. In this research, the methods of observation, interviews and documentation on the subject and those closest to the subject were used as data collection techniques. The subject in this research was a 12-year-old child from the Sapen Muhammadiyah Elementary School, Kraton branch, who was detected to have mild mental retardation, with slow comprehension abilities (slow learner) based on the results of psychological tests. The research results show that the development of religiosity that occurs in subjects has certain characteristics based on the characteristics of their special needs. Optimizing the development of the religiosity of students with special needs in its application requires a long, slow and repetitive process based on habituation and example from those closest to the subject, teachers and parents.